2021
DOI: 10.26451/abc.08.03.08.2021
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Cross-Contextual Consistency in Spatial Cognition or Behavioral Flexibility in a Passerine

Abstract: Although the evolution of cognitive differences among species has long been of interest in ecology, whether natural selection acts on cognitive processes within populations has only begun to receive similar attention. One of the key challenges is to understand how consistently cognitive traits within any one domain are expressed over time and across different contexts, as this has direct implications for the way in which selection might act on this variation. Animal studies typically measure a cognitive domain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 69 publications
0
21
0
1
Order By: Relevance
“…Another factor potentially explaining the lack of consistency is that some tasks that appear very similar to us could in fact be perceived differently by the animals and even rely on different cognitive mechanisms (Cauchoix et al 2018 ). For example, Troisi et al ( 2021 ) showed that learning was not consistent in a spatial learning task between two different spatial scales. They hypothesized that this could be due to allo- vs egocentric navigation and different cue use (Troisi et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another factor potentially explaining the lack of consistency is that some tasks that appear very similar to us could in fact be perceived differently by the animals and even rely on different cognitive mechanisms (Cauchoix et al 2018 ). For example, Troisi et al ( 2021 ) showed that learning was not consistent in a spatial learning task between two different spatial scales. They hypothesized that this could be due to allo- vs egocentric navigation and different cue use (Troisi et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Troisi et al ( 2021 ) showed that learning was not consistent in a spatial learning task between two different spatial scales. They hypothesized that this could be due to allo- vs egocentric navigation and different cue use (Troisi et al 2021 ). This could contribute to the lack of consistency we observe between the high- and the low-stress maze in our study as well, as one of the differences between them is their size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reversal learning tasks measure how quickly and successfully animals adapt to the change of reinforcement contingencies, and has been widely used in testing avian cognition 32 35 . Moreover, reversal learning tasks may reflect inhibitory control because they highlight the capacity to suppress and withhold a learned reward-winning behaviour 31 , 36 , although in great tits ( Parus major ) reversal learning did not correlate with inhibitory control 37 . The behavioural flexibility that characterizes reversal learning may be especially advantageous in complex and stochastic environments 33 , 38 .…”
Section: Introductionmentioning
confidence: 99%